'A Fine Solidarity in the Life of the Countryside': The Ashbees and Sport in the Cotswolds, 1902–1907. Issue 15 (13th October 2021) - Polley, Martin
Abstract: Between 1902 and 1907, C.R. and Janet Ashbee ran the Guild of Handicraft from Chipping Campden in Gloucestershire, a manufacturing and trade experiment underpinned by utopian ideas. They used sport in the life of the Guild and the wider town in various ways, including the construction of a public swimming pool, the promotion of sports days, and the compilation of sporting songs, while their writings – both public and private – on sport revealed underlying assumptions about a sporting culture that diverged from both the commercial and amateur models of sport that were predominant in Edwardian Britain. This model for sport, based on balance, solidarity, community bonds, and health, was evident in all of their interventions in sport. This article, based on the Ashbees' published and unpublished writings, along with Guild and other archives and newspaper reports, explores this sporting culture.